Comparing web-based and blended training for coping with challenges of flexible work designs: randomized controlled trial - Althammer, Sarah Elena; Wöhrmann, Anne Marit; Michel, Alexandra (Journal of medical internet research, 2023)
Background: Workers with flexible work designs (FWDs) face specific challenges, such as difficulties in detaching from work, setting boundaries between work and private life, and recovering from work. Objective: This study evaluated the effectiveness of an intervention in improving the recovery, work-life balance, and well-being of workers with FWDs compared with a waitlist control group. It also compares the effectiveness of a web-based training format and blended training format. Methods: In the web-based training format, participants individually completed 6 web-based modules and daily tasks over 6 weeks, learning self-regulation strategies to meet the particular challenges of FWDs. In the blended training format, participants attended 3 group sessions in addition to completing the 6 web-based modules. In a randomized controlled trial, participants were assigned to a web-based intervention group (196/575, 34.1%), blended intervention group (198/575, 34.4%), or waitlist control group (181/575, 31.5%). Study participants self-assessed their levels of primary outcomes (psychological detachment, satisfaction with work-life balance, and well-being) before the intervention, after the intervention, at a 4-week follow-up, and at a 6-month follow-up. The final sample included 373 participants (web-based intervention group: n=107, 28.7%; blended intervention group: n=129, 34.6%; and control group: n=137, 36.7%). Compliance was assessed as a secondary outcome. Results: The results of multilevel analyses were in line with our hypothesis that both training formats would improve psychological detachment, satisfaction with work-life balance, and well-being. We expected blended training to reinforce these effects, but blended training participants did not profit more from the intervention than web-based training participants. However, they reported to have had more social exchange, and blended training participants were more likely to adhere to the training. Conclusions: Both web-based and blended training are effective tools for improving the recovery, work-life balance, and well-being of workers with FWDs. Group sessions can increase the likelihood of participants actively participating in web-based modules and exercises. Clinical Trial: German Clinical Trials Register DRKS00032721; https://drks.de/search/en/trial/DRKS00032721
Gesehen am 27.08.2024